PCR-Based EST Mapping in Wheat (Triticum aestivum L.) (Biodiversitas Journal of Biological Diversity, 2008)
Mapping expressed sequence tags (ESTs) to hexaploid wheat is aimed to reveal the structure and function of the hexaploid wheat genome. Sixty eight ESTs representing 26 genes were mapped into all seven homologous chromosome groups of wheat (Triticum aestivum L) using a polymerase chain reaction technique. The majority of the ESTs were mapped to homologous chromosome group 2, and the least were mapped to homologous chromosome group 6. Comparative analysisbetween the EST map from this study and the EST map based on RFLPs showed 14 genes that have been mapped by both approaches were mapped to the same arm of the same homologous chromosome, which indicated that using PCRbasedESTs was a reliable approach in mapping ESTs in hexaploid wheat.Key words: wheat, EST, PCR, homologous.